Analisis Batas Kewenangan Antara Penyidik Kepolisian Republik Indonesia Dan BNN Dalam Melakukan Koordinasi Penyidikan Kasus Tindak Pidana Narkotika - Annisa Refi Daenunu; Lisnawaty W Badu; Jufryanto Puluhulawa (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The purpose of this study is to find out how the duties and authorities between Polri investigators and BNN investigators coordinate investigations into narcotics crime cases. Harmonization or coordination is a fabric of collaborative work between law enforcement officials in order to achieve and complete joint tasks, the purpose of this paper is the form of authority exercised by the National Police and BNN in preventing and eradicating the abuse and illicit traffic of narcotics structurally and institutionally in more detail in the field investigation. Based on the results of research, various ways to eradicate Narcotics crime are inseparable from the participation & role of law enforcement officials or in the criminal justice system including the Indonesian National Police, the National Narcotics Agency, the Prosecutor's Office, the Judiciary and anti-narcotics community organizations. In article 6 of the Criminal Code what is meant by investigators are people who are given special authority by law to carry out investigations, including the Indonesian National Police, the National Narcotics Agency and Civil Servants or Assistant Investigators. Law No. 35 of 2009 concerning Narcotics Law enforcers who have the authority to investigate narcotics crimes can be carried out and carried out by BNN investigators & Polri investigators. It is clear that in carrying out this authority one must know what are the limitations in the authority to carry out the authority of both the National Narcotics Agency and the National Police in order to avoid overlapping. Regarding the issues discussed in this study, it is a form of coordination by the Indonesian National Police and the National Narcotics Agency in carrying out investigations into narcotics abuse cases and analyzing the boundaries of authority between the Indonesian National Police and the National Narcotics Agency in preventing and eradicating narcotics crimes in Indonesia. The research method used by researchers is normative juridical research that is analyzed qualitatively or in other words research that uses statutory analysis as primary legal material. Primary Legal Materials such as Books, Scientific Research, Opinions of Experts, Mass Media, Newspapers etc.